2018
DOI: 10.1186/s42358-018-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with diagnosis of early rheumatoid arthritis in the south of Brazil

Abstract: Background: Rheumatoid arthritis (RA) is an autoimmune inflammatory disease characterized by peripheral and symmetrical polyarthritis. It can be divided into Very Early Rheumatoid Arthritis (VERA) diagnosed up to 3 months of symptoms and late onset (Late Early Rheumatoid Arthritis-LERA), diagnosed between 3 and 12 months. Currently, it is recommended to evaluate the patient with joint symptoms as early as possible, and the first 12 weeks of manifestations represent the ideal phase for the diagnosis, favoring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…In Germany, the time between onset of symptoms and presentation to a rheumatologist could be reduced to 9 months [35,36]. In contrast, recent studies in Brazil demonstrated a huge variation of the interval between onset of symptoms and diagnosis of a rheumatic disease, ranging in the REAL study from one to 457 months (median 12 months) and a mean of 28 months in a study from the country's south [32,37]. Both studies show that almost 80% of the RA patients in Brazil were of middle-low or low socioeconomic status, and the delay in diagnosing RA was associated with lower socioeconomic status and lower education level of the patients [38].…”
Section: Discussionmentioning
confidence: 95%
“…In Germany, the time between onset of symptoms and presentation to a rheumatologist could be reduced to 9 months [35,36]. In contrast, recent studies in Brazil demonstrated a huge variation of the interval between onset of symptoms and diagnosis of a rheumatic disease, ranging in the REAL study from one to 457 months (median 12 months) and a mean of 28 months in a study from the country's south [32,37]. Both studies show that almost 80% of the RA patients in Brazil were of middle-low or low socioeconomic status, and the delay in diagnosing RA was associated with lower socioeconomic status and lower education level of the patients [38].…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, most patients with RA were female, brown, with a mean age of 45, data similar to other previously puplished studies. 18,19,20 In our sample, the average age in the 45-year-old range is justi ed by the low inclusion of elderly people, most of whom had already been vaccinated when the project started, in May 2021, making their participation in this cohort unfeasible.…”
Section: Resultsmentioning
confidence: 99%
“…A AR diagnosticada precocemente, ou seja, em até 3 meses após as primeiras manifestações, evidencia uma resposta terapêutica significativamente mais eficaz. Infelizmente, um recente estudo transversal brasileiro concluiu que a realidade para população estudada é bem diferente, sendo o tempo médio até o diagnóstico de 28 meses (GOMES et al, 2018).…”
Section: Aspectos Introdutóriosunclassified